Algorithm for Assessing Learners' Knowledge in Automated Learning Systems - N. Karimov; Sh. Abdurahimov (Zien Journals, 2022)
The article presents the measurement of the arithmetic mean value while the assessment consists of the answers to several questions in the assessment of learners knowledge in an automated learning system, and the assessment algorithm is given
Keywords: Algorithmization; system; teacher; learner